Nutritional Profile and In Vitro Rumen Fermentation of Mixed Silage of Kume Grass and Moringa Leaves - Kleden, Markus Miten; Nenobais, Mariana; Lestari, Gusti Ayu Yudiwati; Ratu, Maria Rosdiana Deno (Jurnal Sain Peternakan Indonesia, 2025)
A study was conducted to determine the nutritional profile and in vitro fermentation characteristics of mixed silage of Kume grass and Moringa leaves in the feed chemistry laboratory, Department of Animal Science, Faculty of Animal Husbandry, Fisheries and Marine, Universitas Nusa Cendana. The materials used were Kume grass and Moringa leaves, with the addition of rice bran as a fermentation stimulant. The research used an experimental method with a completely randomised design consisting of four treatments and five replications. The treatments were the proportions of Kume grass and Moringa leaves, respectively: KK0 = 100% Kume grass + 0% Moringa leaves; KK25 = 75% Kume grass +  25% Moringa leaves;  KK50 = 50% Kume grass + 50% Moringa leaves and KK75 = 25% Kume grass + 75% Moringa leaves. The parameters measured included organoleptic quality, silage nutrient content, in vitro digestibility, and rumen fermentation. The results showed that increasing the level of Moringa leaves resulted in good ensilage, indicated by the absence of mould and a sour aroma. Rising levels of moringa leaves had a statistically significant effect (P<0.01) on the nutrient content of silage, rumen fermentation, and in vitro digestibility of the silage. It can be concluded that ensiling technology using Moringa leaves offers a promising solution to address feed shortages.